Analysis of Green Economy Implementation in The Concept of Money Digitalization in Indonesia - Fitria, Yanisa Zahra Nurul; Asyriyanti, Mulki (Jurnal Wacana Ekonomi, 2023)
In the concept of green economy, an organization creates environmentally friendly ideas, not only pursuing profit, contributing to society (people) and preserving the environment (planet). The Indonesian government pays full attention to new renewable energy by setting the direction of low-carbon development policies, including implementing the digitalization of money. In the field implementation in scalability, network infrastructure is not accessible to everyone, so public interest in the digital economy is still low.  The research method uses qualitative methods with a phenomenological approach to study and convey certain events that occur through coherent literature studies, documentation and secondary data.  The results showed that digitalization of money contributes to society, maintains environmental sustainability and social welfare and encourages increased economic growth, while the constraints on the implementation of the digital payment system are from differences in preferences in the community, facilities and infrastructure supporting the electronic payment system are still uneven, so improvements to the digitalization supporting infrastructure are needed.